Education Of Sharing Culture In The 20th Ramadhan 1443 H – Upmi Share Ta'jil At Mamiyai Orphanage, Jalan Bromo, Medan City - Dewi Robiyanti; Imanuddin Siregar; Ismayani Ismayani; July Esther; Erwin Hamonangan Pane (LEGAL BRIEF, 2022)
This study aims to discuss the phenomenon of sharing ta'jil sharing activities during Ramadan in Indonesia, the study of the science of ma'anil hadith. This research is a qualitative type that applies a literature study by applying the maudhu'i hadith method from a cultural perspective with a phenomenological approach. The results and discussion of this study include the phenomenon of sharing ta'jil during Ramadan in Indonesia, ma'anil hadith sharing takjil during Ramadan, as well as the virtues and benefits of sharing ta'jil. This study concludes that the phenomenon of sharing takjil during Ramadan by people in Indonesia has a positive impact on people who receive ta'jil and has many virtues and benefits for ta'jil givers both in hablumminannas relationships (relationships with fellow human beings) and with habumminallah (relationships with fellow humans) creature with the creator). This study recommends that this simple research be perfected and it is recommended to all Muslims to continue to preserve the phenomenon of sharing ta'jil because there are many benefits and virtues.